(untitled) (Eurasian Research Bulletin, 2022)
Rapid development of small and medium-sized industrial enterprises, rapid construction of rural housing is one of the factors of water pollution, groundwater pollution. In addition to the fact that a large amount of wastewater is drained into the water basin, the preservation of their wastewater is among the important tasks of the municipal economy